Optimalisasi Kepemimpinan Manajerial untuk Kinerja Madrasah Ibtidaiyah Muhammadiyah di Baturetno Wonogiri - Pardi; Abbas, Ngatmin (BISMA : Business and Management Journal, 2024)
The background of this research is the need to improve the performance and development of Madrasah Ibtidaiyah Muhammadiyah in Baturetno District, Wonogiri Regency. The aim of this study is to identify and analyze effective supervision strategies and managerial leadership improvements in supporting the development of the madrasah. This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and relevant document analysis. The research results show that effective managerial leadership, characterized by a clear vision, motivational ability, and good managerial skills, has a significant impact on improving the performance of the madrasah. Furthermore, continuous and participative supervision also proves to be important in supporting the improvement and development of the madrasah. Supervisors who provide active guidance and support help identify and address problems earlier, thus creating a more conducive learning environment. This study concludes that cooperation between the head of the madrasah, teachers, supervisors, and other stakeholders is essential to achieving sustainable development. Support from the government, community, and Muhammadiyah organization is also needed to implement effective managerial leadership improvement strategies. With good cooperation and support, it is hoped that Madrasah Ibtidaiyah Muhammadiyah in Baturetno District can achieve significant improvements in the quality of education.